Preface - Ruddle R. W. (The Institute of Materials, Minerals and Mining, 1953)
Although copper has been smelted for many years, relatively small attempt has been made in the past to examine the fundamental physical chemistry of the processes involved. Therefore, technological developments apart, slow progress has been made with the development of improved or new principles of smelting. The methods at present in use in the majority of the world’s smelters are essentially those employed at the beginning of the present century; it is significant that many of the textbooks on copper smelting, written some 50 years ago, are still regarded as standard works. The book is divided into seven chapters. In the first the fundamentals of modern smelting processes are briefly outlined for easy understanding of the subsequent sections, while the next two chapters are confined to the more theoretical aspects of the constitution of mattes and slags. Some problems of considerable practical importance are discussed in the remaining four chapters; these are (1) magnetite formation, (2) copper losses during smelting, (3) the recovery of sulphur from the smokes produced during smelting, and (4) the elimination of impurities. A collection of thermodynamic data relevant to copper pyrometallurgy is presented in an appendix, and, for the convenience of readers not well acquainted with thermodynamics, a brief explanation of the thermodynamic terms and methods employed is given in a second appendix